2020
DOI: 10.1088/2053-1591/ab654c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defocused plane on entrance and exit hole geometry of high grade steel 18CrNi8 during percussion drilling by Nd:YAG millisecond laser system

Abstract: Modern manufacturing industries prefer laser drilling processes owing to the adequate controlled drilling in comparison with existing alternatives. The presented experimental study mainly accounts defocusing impact along with other technical parameters and optimization of Nd:YAG millisecond pulsed laser drilling; and finally their influence on the entrance and exit holes profile. The key technical parameters such as pulse frequency, pulse width and assisting gas pressure with respect to different defocused foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Moreover, an increase in pressure does not permit the molten metal to set down inside the hole cavity. Thus, hole taper reduces when higher gas pressure is used which is in accordance with the findings of Chatterjee et al 42 A similar trend has been observed with the increase in gas flow rate because higher compressed air flow rate increases the localised temperature due to its combustible supportability and results in efficient removal of the material from the hole exits which results in lower hole taper, as stated by Nawaz et al 20 Influence of pulse energy and pulse duration on drilling cost. Figure 9 illustrates the response of pulse energy and pulse duration on drilling costs.…”
Section: Investigationsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, an increase in pressure does not permit the molten metal to set down inside the hole cavity. Thus, hole taper reduces when higher gas pressure is used which is in accordance with the findings of Chatterjee et al 42 A similar trend has been observed with the increase in gas flow rate because higher compressed air flow rate increases the localised temperature due to its combustible supportability and results in efficient removal of the material from the hole exits which results in lower hole taper, as stated by Nawaz et al 20 Influence of pulse energy and pulse duration on drilling cost. Figure 9 illustrates the response of pulse energy and pulse duration on drilling costs.…”
Section: Investigationsupporting
confidence: 84%
“…The laser processing parameters which affect hole taper include laser pulse duration/ width, pulse energy, assist gas pressure, beam focal position and gas flow rate. [12][13][14][15][16][17][18][19][20] In previous research studies, several authors have explored the effects of these process parameters for single-pulse drilling. Yilbas and Yilbas 21 used the full factorial method to evaluate the impacts of focal position and material thickness on the quality of laser-drilled holes in Nimonic 75.…”
Section: Introductionmentioning
confidence: 99%